2016
DOI: 10.7566/jpsj.85.123701
|View full text |Cite
|
Sign up to set email alerts
|

Low Carrier Density Metal Realized in Candidate Line-Node Dirac Semimetals CaAgP and CaAgAs

Abstract: We study polycrystalline samples of the hexagonal pnictides, CaAgP and CaAgAs, both of which are ideal candidates for line-node Dirac semimetals. The polycrystalline samples of CaAgP and CaAgAs obtained in this study are low-carrier metals, where hole carriers are dominant. By combining the hole carrier densities estimated from Hall coefficients and the electronic structures calculated by first principles calculations, both samples are found to have a ring-torus Fermi surface, derived from a ring-shaped Dirac … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
54
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 49 publications
5
54
2
Order By: Relevance
“…It consists of a 3D-network of edge and corner sharing AgAs 4 tetrahedra. A recent study on polycrystalline CaAgX (X=As, P) revealed that it is a low carrier density metal and that CaAgAs is a more promising candidate than CaAgP for the purpose of studying the nodal lines 28 . Compared to polycrystals, single crystals are superior for transport studies and surface sensitive measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of a 3D-network of edge and corner sharing AgAs 4 tetrahedra. A recent study on polycrystalline CaAgX (X=As, P) revealed that it is a low carrier density metal and that CaAgAs is a more promising candidate than CaAgP for the purpose of studying the nodal lines 28 . Compared to polycrystals, single crystals are superior for transport studies and surface sensitive measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Even for a "conventional" s-wave state, there exists a flat band of neutral Majorana bound states on each surface at the projected location of the FS. Finally, note that while Ca 3 P 2 [10], CaAgP and CaAgAs [12] materials have a four-fold degenerate nodal line (i.e. a Dirac loop), our conclusion can be generalized to these materials.…”
mentioning
confidence: 62%
“…Nodal-line semimetals are a new class of topological materials that has recently been proposed [1][2][3][4][5][6][7][8][9] and observed in Ca 3 P 2 [10], TlTaSe 2 [11], CaAgP and CaAgAs [12]. A Weyl-loop material is the simplest example of these systems which at a particular filling display a two-fold degenerate one-dimensional Fermi ring in the bulk (which becomes toroidal upon doping), with massless Dirac-like quasiparticles.…”
mentioning
confidence: 99%
“…The nodal lines lie on the mirror/glide plane. The spinless nodal-line semimetals have been reported in CaAgP and CaAgAs, which are noncentrosymmetric 36,37 . In general, the protection by the mirror symmetry can coexist with the topological protection.…”
Section: Introductionmentioning
confidence: 99%